2016
DOI: 10.2169/internalmedicine.55.5972
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Case of Lepidic Pulmonary Metastasis from Cholangiocarcinoma

Abstract: We herein report the first case of pulmonary metastasis with lepidic growth that originated from cholangiocarcinoma. A 77-year-old man was admitted to our hospital due to exertional dyspnea and liver dysfunction. Computed tomography showed widespread infiltration and a ground-glass opacity in the lung and dilation of the intrahepatic bile duct. The pulmonary lesion progressed rapidly, and the patient died of respiratory failure. Cholangiocarcinoma and lepidic pulmonary metastasis were pathologically diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…In 1 single-center retrospective analysis, approximately 10% of a single cohort of patients with primary gastrointestinal malignancies (n = 65) demonstrated a lepidic pattern of metastatic disease [6] . Although lepidic pulmonary metastases have also recently been described in the setting of cholangiocarcinoma and combined hepatocellular-cholangiocarcinoma (HCC-CC), to the best of our knowledge, this is the first reported case of lepidic spread of metastatic, poorly differentiated HCC with the thoracic metastases demonstrating acquisition of new pathologic features of cholangiocarcinoma [11] , [12] .…”
Section: Discussionmentioning
confidence: 85%
“…In 1 single-center retrospective analysis, approximately 10% of a single cohort of patients with primary gastrointestinal malignancies (n = 65) demonstrated a lepidic pattern of metastatic disease [6] . Although lepidic pulmonary metastases have also recently been described in the setting of cholangiocarcinoma and combined hepatocellular-cholangiocarcinoma (HCC-CC), to the best of our knowledge, this is the first reported case of lepidic spread of metastatic, poorly differentiated HCC with the thoracic metastases demonstrating acquisition of new pathologic features of cholangiocarcinoma [11] , [12] .…”
Section: Discussionmentioning
confidence: 85%
“…We found that both lesion type and border were significant predictors of primary lung cancer. It is well known that a radiological subsolid pulmonary lesion is one of the typical characteristics of primary lung adenocarcinoma, even though it could also be pulmonary metastasis (in rare cases), such as pulmonary metastasis with lepidic growth . When examining 18 F‐FDG‐PET/CT characteristics, the SUV max cutoff point of 2.5 was a significant predictor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that a radiological subsolid pulmonary lesion is one of the typical characteristics of primary lung adenocarcinoma, 31 even though it could also be pulmonary metastasis (in rare cases), such as pulmonary metastasis with lepidic growth. 3,31 When examining 18 F-FDG-PET/CT characteristics, the SUV max cutoff point of 2.5 was a significant predictor in multivariate analysis. Most FDG-negative lesions were primary lung cancer and all of these patients had adenocarcinoma with subsolid radiological presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Chest CT of pulmonary metastasis from the pancreas, colon, and stomach shows lepidic growth associated with air-space patterns, such as air bronchograms, ground-glass opacities, and consolidation [ 9 ]. Additionally, lepidic pulmonary metastasis from perihilar cholangiocarcinoma was reported in an autopsy case [ 10 ]. In our patient, preoperative chest CT before PD showed an air-space pattern in the upper lobe of the left lung.…”
Section: Discussionmentioning
confidence: 99%